Dampak Keberlanjutan Peternakan Ayam Broiler Pola Kemitraan (Kasus di Pasini Farm, Ciamis) - Pasini, Anggun; Ramadhan, Faisal; Nurhasanah, Sabrina; Firman, Achmad (Universitas Galuh, 2024)
Broiler chickens are one of the livestock commodities that have an important role in fulfilling people's animal protein needs. However, the growth of the broiler farming industry is also followed by several significant negative impacts on the environment, local economy, and public health. This study aims to (1) analyze the environmental impacts of broiler farming, (2) determine community perceptions of the environmental impacts of broiler farming, and (3) analyze the sustainability and sensitive attributes of broiler farming. This study used survey methods, interviews, and secondary data analysis to collect information about the impacts of broiler farming in Pasini Farm. The research respondents were determined by purposive sampling method with the criteria of living around the farm environment within a 2 km radius and 10 informants from Jelat Ciamis Village were selected. Data analysis used in this study was problem tree analysis and descriptive percentage. The results showed that the existence of Pasini Farm broiler farms has made a positive contribution to the local economy, by creating jobs and increasing the income of local farmers and in social contributions helping to develop social communities, infrastructure and provision of animal protein. However, the increase in broiler production has also presented environmental challenges such as water and air pollution and the health problems of the surrounding community.